A Meta-Analytic Review of Naming-Speed Deficits in Developmental Dyslexia. (3rd September 2019) - Araújo, Susana; Faísca, Luís
ABSTRACT: This study presents a meta-analytic review of serial rapid automatized naming (RAN) deficits in individuals with dyslexia relative to typical readers (based on 216 effect sizes comprising 8335 dyslexic readers, 14, 083 age-matched controls, and 921 reading-matched controls). A random-effects model analysis indicated a large impairment in speeded RAN in individuals with dyslexia compared with age-matched controls ( d = 1.19) but a similar performance when compared with reading-matched controls ( d = 0.13). In addition, dyslexic readers presented a deficit in discrete-naming formats ( d = 0.74), although the deficit in serial RAN was notably larger; hence, adding seriality is particularly detrimental for these readers. The deficit appears to span all stimulus types (alphanumeric and nonalphanumeric), indicating that processes beyond letter processing are responsible for the delays and are independent of set size. Poor RAN is a long-term and universal symptom of dyslexia, and the transparency of the writing system does not influence its severity.